Palliative Care in Resource-poor Settings: Inequalities, Challenges, and Opportunities - Dangal, Ganesh; Paudel, Bishnu Datta; Jha, Anjani Kumar (Journal of Nepal Health Research Council, 2018)
Palliative care is, according to WHO,â€œan approach thatimproves the quality of life of patients and their familiesfacing the problems associated with life-threateningillness, through the prevention and relief of sufferingâ€.The need for palliative care is increasing throughout theworld as it is well known that palliative care improvesquality of life for seriously ill patients and their familiesbut the palliative care needs of all patients are beingaddressed inadequately in resource-poor settings.Although developed western world has a rapidly growingsystem in place for palliative care services, clinical,research and educational programs; it is negligible inthe developing countries.